‘Cold intimacies’ in parents’ negotiations of work–family practices and parental leave? - Twamley, Katherine (Sociological Review, 2019)
This article aims to assess the contention that a ‘feminist’ ideology is associated with a ‘cooling’ of intimacy in heterosexual relationships, as argued by scholars such as Arlie Hochschild and Eva Illouz. According to this thesis, such an ideology, ‘abducted’ by a commercial spirit, encourages women to disengage from warm intimate bonds with others and to prioritize their own personal fulfilment and parity in care and housework. Drawing on two qualitative empirical studies exploring couples’ intimate lives and their feminist and egalitarian preferences and practices in leave, care and housework, this article examines in detail the basis of this thesis, and its effectiveness in explaining the lived experiences of parent couples’ negotiations of this terrain. The data were collected through focus group discussions with parents not sharing leave and a detailed ethnography with couples sharing leave. The comparison shows that, far from observing a clear dichotomy between ‘cold’ feminists and ‘warm’ traditional couples, both sets of parents present a more complex picture of ‘warm’ and ‘cold’ relations. The analysis enables a critical appreciation of sociological theorizing about gender equality and intimacy, contributing to sociological debates around individualism, feminism and family life. © The Author(s) 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; congé parental; discipline; europe; maternité; paternité; projet charge mentale; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail de reproduction